The social geography of the estate landscape in Gelders Arcadië (Bulletin KNOB, 2021)
For many centuries, the landscape and cultural history of the Netherlands have been influenced by the rural estates of large landowners. Their country houses with gardens, parks and farmland formed an important combination of practical aspects of economic management and aesthetic landscaping. Many castles or country houses were linked to large landholdings of several hundred, sometimes even thousands of hectares, as in the case of the Veluwezoom in the Province of Gelderland. Since the late Middle Ages this area, now known as Gelders Arcadia, has been popular with the landed elite, whose ranks have included noble families, stadtholders, city regents and bankers. The undulating landscape, the rivers and brooks and the fertile land was ideally suited to the creation of the desired combination of productive and aesthetic landscapes.One of the special aspects of the Gelders Arcadia estate zone is that it represents nearly every stage in the development of the Dutch country estate, from the emergence of castles and lordships (c. 500-1600), to the foundation of small country retreats by town regents (c. 1600-1800), and the creation of villa-like country estates for a new elite of bankers, industrialists and lawyers (c. 1800-1940). The historic country houses and landed estates are manifestations of their time and therefore very diverse, ranging from transformed noble castles with large landholdings to the rural retreats of town regents to villa-like country houses for the newly wealthy. Not only the architecture of the house and park, but also the use, the anchoring in the cultural landscape and the social significance underwent development.A historical-geographical approach was used to analyse location and distribution patterns and to investigate the size, character and functions of country estates in each period from an economic, political, societal and social perspective. It appears that the majority of new country houses and estates were created by a new elite of the newly rich, whereas the old elite continued to invest in their ancestral properties.The motivation to invest in the establishment of a country seat differed per period. The landed and country estates featured both economic and aesthetic landscapes, although the former were less prominent in later periods.This socio-historical-geographical approach has given us a better understanding of the various processes of estate creation, transformation and adaptation through time – knowledge that can also be used to reach well-founded decisions in the 21st century. The geographical approach for Gelders Arcadia has resulted in improved spatial policies through: 1. Attention to the entirety of country estates (rather than only those with listed status); 2. A focus on the country estate as a cohesive heritage ensemble, including an understanding of the social, economic, landscape and political factors that contributed to its development and design; 3. Recognition that the estates, thanks to their large number and individual sizes and qualities, have formed and will continue to form an important basis for the character of the living environment.